Pengujian Karakteristik Turbin Angin Tipe Horizontal Sudu Flat Multiblade Dengan Pengaturan Sudut Sudu - Syafriyudin Syafriyudin; M Suyanto; Subandi Subandi; M Nurkhakim W (Journal of Electrical Power Control and Automation (JEPCA), 2020)
One effort to overcome the energy crisis is to utilize wind energy as a power source. Angina power Plant is a method for generating electrical energy by rotating the angina turbine connected with the generator, the electric energy produced by the generator is stored in an element of electric energy storage (battery). The next one will be channeled to load center like household. The Perarancangan of the horizontal type flat Multiblade Sudu is using a microcontroller that can change the angle of the sudu according to the wind speed so as to maximize the power of wind potential energy. For a sudu angle setting that can adjust the speed of the wind, use two servo motors that have been control by the Arduinouno from the input anemometer so that the angle of the sudu can adjust the wind speed. The results have shown that the turbine-angle arrangement of the turbines can increase the rotation of the wind turbine, thereby increasing the voltage raised in the generator. The optimal angle of the Sudu is at a 15o angle, at a wind speed of 9.5 m/s, resulting in a turbine round of 610 rpm.